Polarization reconfigurable suspended antenna using RF switches and P-I-N diodes - Boonying, Komkris; Phongcharoenpanich, Chuwong; Kosulvit, Sompol (My University, 2014)
Polarization reconfigurable square flat antenna using RF switches and P-I-N diodes is presented for WLAN application operated at the center frequency of 2.45 GHz. The proposed antenna consists of the square flat structure, three switches (six P-I-N diodes), transmission-line phase shifters of 0 and 90 degrees. The antenna can be switched between 5 different states: vertical, horizontal and slant polarizations for linear polarization (LP), left-handed circular polarization (LHCP) and right-handed circular polarization (RHCP) by controlling the DC bias of 5 V and the current of 16 mA for the P-I-N diodes. The simulated and measured results show that the proposed antenna can cover the impedance bandwidth from 2.400 GHz to 2.484 GHz and good axial ratio for the circular polarization. © 2014 IEEE.
Keywords: P-i-n diode; Polarization; Reconfigurable antenna; RF switch